Revised to amine-based solvent systems: an integrated review with a focus on CESAR-1 - Kim, Dongseok; Park, Alex (Technium BioChemMed, 2025)
Carbon dioxide (CO₂) emissions are widely recognized as meaningful contributors to climate change and global warming. Technologies of various kinds have been proposed to address this issue, and among them, amine-based solvents are widely utilized. However, monoethanolamine (MEA), the prototypical amine-based solvent, exhibits critical limitations due to its relatively higher energy consumption compared to recent developments, as well as corrosion, degradation, and carcinogenic byproducts. CESAR-1, a mixture of AMP (2-amino-2-methyl-1-propanol) and PZ (piperazine), is consequently proposed as an alternative solution. This paper presents a comparative analysis of MEA, MDEA, and CESAR-1 while highlighting their structural properties, reaction pathways, CO₂ absorption capacity, regeneration energy requirements, and by-product formation. Previous research had compiled CO₂ reaction pathways and outcomes for each solvent under varying conditions, encompassing reaction of both absorption and regeneration, and by-product formation. MEA has been commercially used and can operate continuously for over 4,000 hours, as demonstrated in numerous studies. Continuous operation enabled these studies to yield highly reliable results. However, MEA has high energy consumption, which significantly increases operating costs. In other words, it greatly reduces efficiency. Based on a comprehensive review of the materials provided, CESAR-1 is particularly noteworthy because of its synergistic strengths of AMP and PZ, which somewhat negate the disadvantage of MEA. Nevertheless, drawbacks remain in CESAR-1; hence, we proposed an alternative by introducing Selective Catalytic Reduction (SCR). SCR may be a suitable strategy for reducing the formation of nitrosamines during the process. However, as NO and NO₂ pose greater environmental and health risks than CO₂, further studies are required to determine which by-products emitted from the entire process are not hazardous to the environment.